The Position of Amicus Curiae under the Indonesian Law of Evidence - Aulia, Fadil; Muksin, Muchlas Rastra Samara (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2020)
The use of amicus curiae has been common in Indonesia, especially in criminal courts. Although there is no clear regulation on amicus curiae, in practice, it has been submitted more than 24 times to the courts. Even there are some judges who consider amicus curiae in making their decisions. This paper aims to determine and examine the legal standing and the strength of amicus curiae under the Indonesian law of evidence. This normative legal research relies on the secondary data in the form of legal material. It is found that the opinion of an amicus curiae, which is usually submitted to the court in written form, could be used as a documentary evidence as intended in Article 187 of the Criminal Procedure Code. However, it has no binding force. Therefore, the judges are free whether or not to consider the opinion submitted by the amicus curiae.